Inhibition efficiency of silver nanoparticles solution on corrosion of mild steel, stainless steel and aluminum in 1.0 M HCl medium. Issue 1 (March 2020) - Asafa, TB; Odusote, JK; Ibrahim, OS; Lateef, A; Durowoju, MO; Azeez, MA; Yekeen, TA; Oladipo, IC; Adebayo, EA; Badmus, JA; Sanusi, YK; Adedokun, O
Abstract: Research work on corrosion behaviour of metals and their alloys continues to attract considerable attention because of the huge cost required to prevent corrosion and replace failed or contaminated components due to corrosion reactions. Different inhibitors have been used to minimize corrosion rate, but addition of nanoparticles has been reported to enhance inhibition efficiency. In this work, the influence of silver nanoparticles (AgNPs) on inhibition of corrosion of mild steel, stainless steel and aluminum in 1.0 M HCl were investigated. Biosynthesized AgNPs were acquired from Laboratory of Industrial Nanobiotechnology, Ladoke Akintola University of Technology Ogbomoso. The particles were hitherto characterized using FTIR, UV-Vis and TEM. Five concentrations of AgNPs solution (0, 5, 10, 15, and 20 μg/ml) were added to 1.0 M HCl. The corrosion inhibition effects of the AgNPs on the metal samples were analyzed using gravimetric (weight loss), potentiodynamic polarization and gasometric (hydrogen gasevolution) approaches. Gravimetric study was conducted within 2000 h of exposure, and the results showed that weight loss increased with exposure time but decreased with increased concentration of AgNPs solution. In addition, inhibition efficiency was enhanced by the addition of AgNPs solution; 52% for mild steel, 70% for stainless steel and 62% for aluminum. Gasometric results revealed that the volume of hydrogen gas evolution reduced with increased exposure time and concentration of AgNPs solution. Furthermore, potentiodynamic polarization results showed that the presence of AgNPs modified the mechanism of anodic dissolution and cathodic hydrogen gas evolution. These results indicated that AgNPs can be incorporated into the existing inhibitors towards minimizing corrosion rate.